The Gambia : 2005 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that The Gambia's economic performance since the mid-1980s has been uneven owing to exogenous shocks, macroeconomic and structural policy slippage, poor governance, and weak institutions. The economic performance has been constrained by policy distortions and by recurrent weaknesses in fiscal policy. Expansionary policies have increased the government's recourse to domestic bank financing, which, in turn, has raised real interest. Macroeconomic performance has strengthened over the past 18 months particularly through end-2004, in response to strong financial policies.